Evaluation and improvement of the training program for rotating year level V medical students in a general surgery division in the Philippine General Hospital and the University of the Philippines College of Medicine - Joson, Reynaldo O.
A project was undertaken that focuses primarily on the change process in medical education and secondarily, on the development of a curriculum. The project involves the training program of the Division of Head and Neck, Breast, Esophagus, and Soft Tissue Surgery of the Philippine General Hospital for rotating Year Level V medical students from the UP College of Medicine. There were essentially four parts in the project: 1) The first part consisted of an evaluation of the existing training program to determine initially and then to convince the Division's staff the need for a change. Questionnaire was used to feel the pulse of the students and the answers were then presented to the Division's staff. The decision of the staff was to improve the curriculum for these students. The second part consisted of a development of an improved curriculum. This part started with a review of the Department of Surgery's and the Division's existing curricula. After the review, guidelines in the design of the new curriculum were set up. These guidelines consisted of the following: 1) It must be in consonance with the Department's curriculum, 2) It must be feasible within the time allotted by the Department; 3) It must take into considerations the needs of the students; 4) It must be effective, 5) It must be sustainable. The new curriculum was then developed and later approved by the Division's staff. A summative evaluation plan was also developed at this stage even before the implementation. This was intended to polish the curriculum as well as to facilitate post-implementation evaluation. Production and reproduction of training materials and evaluation forms as well as training of resident-facilitators were accomplished before the implementation proper. The third part consisted of the implementation. The new curriculum was implemented for five small groups of Year Level V medical students from August 30, 1993 to October 3, 1993. Six residents served as faculty. The implementation was accomplished without any major hitch. The last part consisted of the summative evaluation of the new curriculum. Criteria of merit used were effectiveness and sustainability. Analysis of data showed the two criteria were achieved. In this project, the following steps were undertaken in the change process: 1) Recognition of the need for change, 2) Diagnosis of the problem, 3) Identification of the alternative methods and strategies, 4) Selection of the method and strategy which constituted the curriculum development proper, 5) Overcoming of barriers to change, 6) Implementation of the change, 7) Evaluation of the change. The next step to be done is the institutionalization of the change.